Healthcare Quality Indicators for Physiotherapy Management in Hip and Knee Osteoarthritis and Rheumatoid Arthritis: A Delphi Study. (22nd January 2016) - Peter, W. F.; Hurkmans, E. J.; van der Wees, P. J.; Hendriks, E. J. M.; van Bodegom‐Vos, L.; Vliet Vlieland, T. P. M.
Abstract: Objectives: The aim of the present study was to develop healthcare quality indicators (HCQIs) for the physiotherapy (PT) management of patients with hip or knee osteoarthritis (HKOA) or rheumatoid arthritis (RA) in the Netherlands. Methods: Two multidisciplinary expert panels, including patients, were instituted. A draft HCQI set was derived from recommendations included in two existing Dutch PT guidelines for HKOA and RA. The panels suggested additional topics, after which a Delphi procedure was performed. All propositions were scored for their potential to represent good‐quality PT care (score range 0–9). Based on predefined rules, the Delphi panel HCQIs were discussed and selected. Lastly, every indicator was rephrased, resulting in its output consisting of a numerator and denominator, to facilitate comparisons within and among practices. Results: After two Delphi rounds, two final sets of 17 HCQI – one for HKOA and one for RA – were composed, both containing 16 process indicators (regarding initial assessment, treatment and evaluation) and one outcome indicator. Conclusions: Two sets of HCQIs for PT management in HKOA and RA were developed for measuring the quality of PT care in daily clinical practice. Each indicator was formulated in a measurable way. Future research should focus on the feasibility of both indicator sets for daily clinical practice.